Drosophila MIC10b can polymerize into cristae-shaping filaments - Stephan, Till; Stoldt, Stefan; Barbot, Mariam; Carney, Travis D.; Lange, Felix; Bates, Mark; Dib, Peter Bou; Inamdar, Kaushik; Shcherbata, Halyna R.; Meinecke, Michael; Riedel, Dietmar; Dennerlein, Sven; et al. (Life science alliance, 2024)
Cristae are invaginations of the mitochondrial inner membrane that are crucial for cellular energy metabolism. The formation of cristae requires the presence of a protein complex known as MICOS, which is conserved across eukaryotic species. One of the subunits of this complex, MIC10, is a transmembrane protein that supports cristae formation by oligomerization. In Drosophila melanogaster, three MIC10-like proteins with different tissue-specific expression patterns exist. We demonstrate that CG41128/MINOS1b/DmMIC10b is the major MIC10 orthologue in flies. Its loss destabilizes MICOS, disturbs cristae architecture, and reduces the life span and fertility of flies. We show that DmMIC10b has a unique ability to polymerize into bundles of filaments, which can remodel mitochondrial crista membranes. The formation of these filaments relies on conserved glycine and cysteine residues, and can be suppressed by the co-expression of other Drosophila MICOS proteins. These findings provide new insights into the regulation of MICOS in flies, and suggest potential mechanisms for the maintenance of mitochondrial ultrastructure.